2020
DOI: 10.1002/jsfa.10848
|View full text |Cite
|
Sign up to set email alerts
|

Humic acid as foliar and soil application improve the growth, yield and quality of coffee (cv. C × R) in Western Ghats of India

Abstract: BACKGROUND Humic acid is a promising natural resource to be utilized as an alternative for increasing soil fertility and crop production. A field experiment was conducted on the loamy sand soil at the Central Coffee Research Institute research farm, Karnataka, India for 2 years to evaluate the influence of humic acid on yield and bean quality of coffee with six treatments. The treatments comprised of recommended dose of fertilizer (RDF), humic acid soil application and foliar spray along with nutrient mixture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
(39 reference statements)
1
1
0
Order By: Relevance
“…Pramanik and Sanmay (2016) indicated that increases in the total number of nodes/branches, number of bearing nodes/branches, number of fruits/branches and fruit set percentage resulted in improvements in yield. These results agree with the results of Mote et al (2020) and Gokavi et al (2020), who observed a positive and significant correlation between the yield parameters and coffee yield.…”
Section: Discussionsupporting
confidence: 93%
“…Pramanik and Sanmay (2016) indicated that increases in the total number of nodes/branches, number of bearing nodes/branches, number of fruits/branches and fruit set percentage resulted in improvements in yield. These results agree with the results of Mote et al (2020) and Gokavi et al (2020), who observed a positive and significant correlation between the yield parameters and coffee yield.…”
Section: Discussionsupporting
confidence: 93%
“…Although foliar-applied sedimentary humic acid significantly increased shoot and root growth, it had no effect on the levels of nutrients in the leaves. Kishor et al. (2021) and Hernandez et al.…”
Section: Discussionmentioning
confidence: 99%
“…También se han usado datos oficiales por provincia del rendimiento del cultivo de café, para ajustar parámetros de modelos calculados que entregan como respuesta dicha variable objetivo, en kg/ha o ton/ha (39), es decir, en cada variación de un atributo, los rendimientos pronosticados se compararon con los observados hasta que se encontraron las mejores combinaciones (48), en otras palabras, el modelo cuyos resultados entregó menos errores. Además, se ejecutó una evaluación visual para verificar qué tan bien el modelo simula la variabilidad del rendimiento interanual observada.…”
Section: Variable Objetivounclassified
“…Variables obtenidas satelitalmenteQuímicas (ver tabla 10): Otro de los componentes más relevantes en la productividad de los cultivos de café es su mantenimiento químico; la variación de la cantidad de nutrientes que recibe la tierra es crucial para las cosechas futuras (44)(41), algunos de los elementos más utilizados, medidos comúnmente en mol/l, son: magnesio, hierro, calcio, boro, nitrógeno, fosforo y potasio, junto con los niveles de pH en el suelo y los nutrientes del suelo evaluados por los niveles de carbono orgánico presentes en la muestra (37) (47)(35). Se observa como en la mayoría de los artículos evaluados, el rendimiento del café Robusta está principalmente limitado por la disponibilidad de nitrógeno (29), también algunas combinaciones optimizan la producción(38), así como la implementación de insumos de nutrientes orgánicos como la hojarasca y sintéticos: acido húmico (kg / acre) y urea(48). Otros análisis más detallados se presentan en (44) donde a algunas de las variables descritas antes se le suman: Ca…”
unclassified